Investments in the cryptocurrency market or the commodity exchange. Which is more efficient? - Sylwester Kozak (Malopolska School of Economics in Tarnow, Poland, 2021)
Cryptocurrencies have become an essential element of the global financial system, and in recent years also a frequent investment tool. The aim of the study is to check whether investments in cryptocurrencies are more effective than in commodities on commodity exchanges. The study was conducted based on the daily quotations of the analyzed instruments in 2011–2020. The investment efficiency level was estimated using Sharpe’s and Sortino’s indicators. The research results showed that, on average, over the entire period under study, investments in cryptocurrencies were burdened with the highest risk, but at the same time achieved the highest daily rates of return. As a result, they were much more effective investment tools than gold, silver and WTI. The advantage of cryptocurrencies could be due to the long-term persistence of ultra-low interest rates and the reduced attractiveness of investment in debt securities. Bitcoin and etherum with the largest shares in cryptocurrency market capitalization have proven to be the most effective investment tools.